Na+ Channel β Subunits: Overachievers of the Ion Channel Family - Brackenbury, William J.; Isom, Lori L. (Frontiers in Pharmacology, 2011)
Voltage gated Na+ channels (VGSCs) in mammals contain a pore-forming α subunit and one or more β subunits. There are five mammalian β subunits in total: β1, β1B, β2, β3, and β4, encoded by four genes: SCN1B-SCN4B. With the exception of the SCN1B splice variant, β1B, the β subunits are type I topology transmembrane proteins. In contrast, β1B lacks a transmembrane domain and is a secreted protein. A growing body of work shows that VGSC β subunits are multifunctional. While they do not form the ion channel pore, β subunits alter gating, voltage-dependence, and kinetics of VGSC α subunits and thus regulate cellular excitability in vivo. In addition to their roles in channel modulation, β subunits are members of the immunoglobulin (Ig) superfamily of cell adhesion molecules (CAMs) and regulate cell adhesion and migration. β subunits are also substrates for sequential proteolytic cleavage by secretases. An example of the multifunctional nature of β subunits is β1, encoded by SCN1B, that plays a critical role in neuronal migration and pathfinding during brain development, and whose function is dependent on Na+ current and γ-secretase activity. Functional deletion of SCN1B results in Dravet Syndrome, a severe and intractable pediatric epileptic encephalopathy. β subunits are emerging as key players in a wide variety of pathophysiologies, including epilepsy, cardiac arrhythmia, multiple sclerosis, Huntington’s disease, neuropsychiatric disorders, neuropathic and inflammatory pain, and cancer. β subunits mediate multiple signaling pathways on different timescales, regulating electrical excitability, adhesion, migration, pathfinding, and transcription. Importantly, some β subunit functions may operate independent of α subunits. Thus, β subunits perform critical roles during development and disease. As such, they may prove useful in disease diagnosis and therapy.